ANALISIS PENGGUNAAN HANDPHONE PADA ANAK KELAS 6 SAAT PEMBELAJARAN DI SDN KEMAYORAN 1 BANGKALAN - Ajeng Kartika Valentina; Isna Ida Mardiyana; Siska Trisnayanti (CV. ADIBA ASIHA AMIRA, 2024)
The aim of this research is to analyze the use of cellphones by grade 6 children during learning at UPTD SDN Kemayoran 1 Bangkalan Regency. The method used in this research is a descriptive qualitative method. According to Meleong (2011:6), qualitative research is a method that aims to understand phenomena experienced by research subjects, such as behavior, perceptions, motivations, actions, and so on, holistically and describe them in the form of words and language in a natural context. using various appropriate methods.